The trypanosome Pumilio-domain protein PUF7 associates with a nuclear cyclophilin and is involved in ribosomal RNA maturation - Droll, Dorothea; Archer, Stuart K.; Fenn, Katelyn; Delhi, Praveen; Matthews, Keith; Clayton, Christine (FEBS letters, 2010)
Proteins with Pumilio RNA binding domains (Puf proteins) are ubiquitous in eukaryotes. Some Puf proteins bind to the 3′-untranslated regions of mRNAs, acting to repress translation and promote degradation; others are involved in ribosomal RNA maturation. The genome of Trypanosoma brucei encodes eleven Puf proteins whose function cannot be predicted by sequence analysis. We show here that epitope-tagged TbPUF7 is located in the nucleolus, and associated with a nuclear cyclophilin-like protein, TbNCP1. RNAi targeting PUF7 reduced trypanosome growth and inhibited two steps in ribosomal RNA processing.
Gesehen am 20.02.2023